The Influence of Brand Image, Product Quality, and Price on Customer Satisfaction Mediated by Purchase Decision of New Balance Shoes in Palu City - Natalia, Agnes; Rombe, Elimawaty; Syarifuddin, Umar; wanti, Sri (JURNAL MANAJEMEN MOTIVASI, 2025)
This research examines the effect of brand image, product quality, and price on customer satisfaction for New Balance shoes in Palu City, with purchase decision as a mediating variable. Using a sample of 96 respondents and analyzed through Partial Least Square-Structural Equation Modeling (PLS-SEM), the results indicate that brand image, product quality, and price have a significant positive effect on satisfaction. The purchase decision variable also mediates these relationships. The findings offer valuable insights for New Balance to formulate data-driven marketing strategies, improve customer satisfaction, and build brand loyalty amid increasing market competition, especially in local consumer segments such as Palu City.